Regulatory arbitrage in relation to international human rights - Minhat, Marizah; Abdullah, Mazni; Dzolkarnaini, Nazam (Taylor & Francis, 2019)
The adoption of the United Nations (UN) Charter in 1945 marked the legalization of international human rights. Despite the legalized status of human rights, their violation by states is not uncommon. This article questions why a state might violate international human rights. Analyzing this issue from an economic perspective, this article advances regulatory arbitrage theory to rationalize a state’s violation of human rights. It discusses regulatory arbitrage-type behaviors among state actors that derogate from the obligations to respect, protect, and fulfill human rights. Defending state sovereignty, minimizing regulatory or compliance costs, and prioritizing economic achievement are identified as rational arbitrage actions that circumvent international human rights. We call for competent and credible governance mechanisms that can increase the cost of arbitrage, to disincentivize state violation of international human rights. © 2019, © 2019 The Author(s). Published with license by Taylor & Francis Group, LLC.